1959
DOI: 10.1080/00288233.1959.10418029
|View full text |Cite
|
Sign up to set email alerts
|

Effect of phosphate topdressing on a soil from Andesitic Volcanic Ash

Abstract: SummaryA comparison has been made within a single soil type, New Plymouth black loam, of soils collected from farms that differed in their phosphate topdressing management: (a) not topdressed; (b) topdressed for 25 years at 20-30 Ib P/acre/year; (c) topdressed for the last seven years at 60-80 Ib P /acre/year. Total, organic, apatite and Fe-and Al-bound phosphorus has been determined in these soils and also phosphorus soluble in dilute acids and neutral ammonium fluoride.Phosphate topdressing has had !ittle ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1963
1963
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…AI-P is often observed to be a major fraction in which P~ accumulates in fertilised pasture soils (Batten et al, 1979;Saunders, 1959), but such a marked accumulation of P as Ca-P is less typical. However, Condron and Gob (1989) suggested that liming the site in 1962 would have tended to favour the formation of Soil P fractions in grazed pasture 131 calcium phosphate compounds as reaction products following dissolution of superphosphate whilst the use of superphosphate with an unusually high proportion of unreacted apatite during the 1970's would have favoured accumulation of residual apatite.…”
Section: Discussionmentioning
confidence: 99%
“…AI-P is often observed to be a major fraction in which P~ accumulates in fertilised pasture soils (Batten et al, 1979;Saunders, 1959), but such a marked accumulation of P as Ca-P is less typical. However, Condron and Gob (1989) suggested that liming the site in 1962 would have tended to favour the formation of Soil P fractions in grazed pasture 131 calcium phosphate compounds as reaction products following dissolution of superphosphate whilst the use of superphosphate with an unusually high proportion of unreacted apatite during the 1970's would have favoured accumulation of residual apatite.…”
Section: Discussionmentioning
confidence: 99%
“…Because this soil is also potassium-deficient regular potassium top-dressing is needed, and phosphate and potassium are usually added as potassic super. Saunders and Metson (1959) have suggested that the best utilisation of soluble potassium fertilisers is obtained by split dressings. It therefore becomes desirable to add potassium separately from phosphate except in late summer.…”
Section: Discussionmentioning
confidence: 99%